Controle et adaptation des calculs elements finis pour les problemes de contact unilateral - Coorevits, Patrice; Hild, Patrick; Pelle, Jean-Pierre (European Journal of Computational Mechanics, 1999)
In this paper, we present an error estimator for the contact problem of an elastic body on a rigid foundation in elasticity or Signorini’s problem. The estimator is based on the concept of error in the constitutive relation and on techniques of admissible fields building. It is carrying into effect with a particular technique in order to take into account the contact. The convergence rate of this estimator is studied. By using procedures of mesh adaptivity previously developed, we show an example of optimized computations for discretizations with 3-nodes triangles.